Is There a Text on This Screen? Reading in an Era of Hypertextuality - Bertrand Gervais (A companion to digital literary study, 2008)
Does a literary text retain the same status once it has become virtual? What is the status of any text in today's era of hypertexts and linked computers? What type of materiality are we dealing with? What forms of reading, what forms of knowledge? We are confronted with increasingly different forms of texts produced with the aid of computers. More often than not, these texts exist only on the internet. They are often animated, filled with sounds and images, accessible through a network, related to one another by hyperlinks, and inscribed in complex environments. How do we manipulate texts that seem to be in a fluid state, that constantly shift; how do we understand them, interpret them?
Keywords: hypertexte; lecture à l'écran